Profiling the T Cell Receptor Alpha/Delta Locus in Salmonids - Edholm, Eva-Stina; Fenton, Christopher Graham; Mondot, Stanislas; Paulssen, Ruth H.; Lefranc, Marie-Paule; Boudinot, Pierre; Magadan, Susana (Frontiers in Immunology, 2021)
In jawed vertebrates, two major T cell populations have been characterized. They are defined as α/β or γ/δ T cells, based on the expressed T cell receptor. Salmonids (family Salmonidae) include two key teleost species for aquaculture, rainbow trout (Oncorhynchus mykiss) and Atlantic salmon (Salmo salar) which constitute important models for fish immunology and important targets for vaccine development. The growing interest to decipher the dynamics of adaptive immune responses against pathogens or vaccines has resulted in recent efforts to sequence the immunoglobulin (IG) or antibodies and T cell receptor (TR) repertoire in these species. In this context, establishing a comprehensive and coherent locus annotation is the fundamental basis for the analysis of high-throughput repertoire sequencing data. We therefore decided to revisit the description and annotation of TRA/TRD locus in Atlantic salmon and two strains of rainbow trout (Swanson and Arlee) using the now available high-quality genome assemblies. Phylogenetic analysis of functional TRA/TRD V genes from these three genomes led to the definition of 25 subgroups shared by both species, some with particular feature. A total of 128 TRAJ genes were identified in Salmo, the majority with a close counterpart in Oncorhynchus. Analysis of expressed TRA repertoire indicates that most TRAV gene subgroups are expressed at mucosal and systemic level. The present work on TRA/TRD locus annotation along with the analysis of TRA repertoire sequencing data show the feasibility and advantages of a common salmonid TRA/TRD nomenclature that allows an accurate annotation and analysis of high-throughput sequencing results, across salmonid T cell subsets.